Capital social e desenvolvimento territorial endógeno: desafios e perspectivas para a criação de um geoparque em Caçapava do Sul, RS (Brasil) - Degrandi, Simone Marafiga (2018)
The present thesis, based on the theoretical contribution provided by endogenous development and social capital, discusses Geotourism and the creation of a Geopark as a territorial development strategy for Caçapava do Sul (RS, Brasil), based on authentic tourism initiatives designed and developed by the local community for the generation of work and income. The study is based on qualitative research and the instruments and techniques used were bibliographic and documentary research, field work, structured interviews, asystematic observation, field diary and photographic record. The research results show that in the last 20 years some initiatives developed by the local community have sought to take advantage of the geopatrimonial potential of the territory for the development of tourism. Among these initiatives are the inns and campsites located next to the important geopatrimônios of the territory, as well as adventure sports groups that use these places to practice their activities. Some important civil society associations, such as the Association for the Development of Geotourism (AGEOTUR), have also been trying to organize themselves to support the development of this activity in the territory. The development of handicrafts and typical products have strong links with the culture and the local landscape, demonstrating the productive potential of the community for the elaboration of geoproducts. In general, after analyzing the interviews and the data collected in the field, it can be concluded that Caçapava do Sul has characteristics that indicate the existence of a good level of mobilization of social capital, but with possibilities to increase even more the use of this type of resource, indispensable for endogenous territorial development. On the other hand, it is observed that there is little communication and articulation between the institutions, Associations that work with the management and planning of tourism in the territory. In addition, there is a need for greater support and investments from public authorities for the infrastructure necessary for the development of Geotourism, since weaknesses are observed in relation to the availability of information to tourists, the hiring of professionals specialized in tourism, improvements in access and accessibility to places of Geoturism interest, among other problems.